The sensitivity coefficients for dynamic systems described by nonlinear difference interconnected ordinary equations and generalized equations with the distributed memory - Rouban, Anatoly I. 1943- (Вестник Томского государственного университета. Управление, вычислительная техника и информатика)
The variation method of calculation of sensitivity coefficients connecting first variation of quality functional with variations of variable and constant parameters for multivariate non-linear dynamic systems described by nonlinear interconnected ordinary difference equations and generalized difference equations with the distributed memory on phase coordinates and variable parameters is developed. The nonlinear quality functional has also a gene-ralized form. Sensitivity coefficients are components of variation of generalized sensitivity functional and they are before variations of variable and constant parameters. The base of sensitivity coefficients calculation are the decision of object equations in the forward direction of discrete time and corresponding difference conjugate equations for Lagrange’s multipliers in the opposite direction of discrete time.